Sensors: Sensitive and Reversible Detection of Methanol and Water Vapor by In Situ Electrochemically Grown CuBTC MOFs on Interdigitated Electrodes (Small 29/2017). Issue 29 (August 2017) - Sachdeva, Sumit; Venkatesh, Manjunath R.; Mansouri, Brahim El; Wei, Jia; Bossche, Andre; Kapteijn, Freek; Zhang, Guo Qi; Gascon, Jorge; de Smet, Louis C. P. M.; Sudhölter, Ernst J. R.
Abstract : In article number1604150, by L. C. P. M. de Smet and co‐workers, CuBTC metal–organic framework (MOF) films are grown directly onto a micro‐structured Cu transducer surface in a fast and controllable way by making use of the anodic dissolution of Cu ions in the presence of organic BTC linkers. Reversible capacitive response to methanol and water vapors is shown, while time‐dependent capacitive responses are successfully simulated by diffusion‐controlled kinetics, and equilibrium capacitive responses follow the Langmuir adsorption model.